Pengaruh Harga Ms Glow terhadap Kepuasan Konsumen - Dewi, Chandra Puspita (Keizai, 2022)
As people's spending power rises, so does the scope of the cosmetics industry, which is benefiting from advances in technology and more cutting-edge variations of existing products. Because of this, cosmetic manufacturers in Indonesia are now able to compete fairly in the local cosmetic brand section in Indonesia. This is due to the fact that demand has been on the rise over the past two years, which has led to an increase in the number of people purchasing cosmetics within Indonesia. The purpose of this research is to investigate the relationship between the pricing of Ms. Glow cosmetic items and the level of customer satisfaction with regard to product quality control factors. Quantitative study was conducted, and a total of one hundred people from the city of Sampit who had previously purchased Ms. Glow goods served as responders. In this study, the method of sampling that was carried out was known as snowball sampling. It is possible to draw the conclusion that there is a positive and significant effect of price on consumer satisfaction based on the findings of this study, which indicate that the value of the sig t-test was 0.000, which means that the significance level was less than 0.05. This indicates that there is a correlation between the price of a product and the degree to which customers are satisfied with that product.